The Effectiveness of Users of the People's Crossing Bridge (JPO) at the Youth Center of the City of North Jakarta Administration during the COVID-19 Pandemic - Isradi, Muhammad; Andri, Maulika Alifia; Rifai, Irfan; Mufhidin, Amar (PT ARRUS Intelektual Indonesia, 2022)
The current dense population of DKI Jakarta must be balanced with the provision of adequate transportation facilities and infrastructure. The current presence of pedestrians is usually concentrated in public facilities such as terminals, shopping centers, educational centers, and other public facilities. The existence of these pedestrians requires facilities for pedestrians, including road crossing facilities such as the People's Crossing Bridge (JPO), where the JPO is installed if it is required that there is no intersection between the flow of pedestrians and the flow of traffic. So that pedestrians want to use the JPO, it must be guaranteed safety and walking distance so that it does not get too far away. For this reason, this study was carried out to determine the effectiveness of the People's Crossing Bridge in the Youth Bracelet of the North Jakarta Administration. To determine the effectiveness of the pedestrian bridge at the Youth Center of North Jakarta City, the researchers observed the number of pedestrians for 2 days, namely during peak hours such as in the morning at 06.00 - 08.00 and in the afternoon at 16.00 - 18.00. From the results of the research for 2 days in the field, it was found that almost 58% of people did not use JPO facilities, and only 42% of people used JPO facilities. Thus, it can be concluded that JPO at the Youth Center of North Jakarta City Administration is classified as a fairly effective JPO.